Development of projection X-ray microscope with 100 nm spot size. Issue 5 (3rd September 2022) - Matsunaga, Norihito; Sato, Tomoya; Higuchi, Kota; Yamada, Atsushi
ABSTRACT: A projection X-ray microscope useful for industrial non-destructive inspections and various biological observations has been developed. By installing a Schottky type electron source, a nano focus X-ray source with 100 nm focal spot size that is easy to handle in various laboratories is successfully achieved at 20 to 80 kVp. An imaging system has been composed of a vertical type that can adjust a sample position on the optical axis, and high-resolution imaging can be achieved by using a high precision stage unit. A test chart with 200 nm line width can be clearly confirmed by a transmission image, and CT images with high spatial resolution were also obtained for a test sample of glass containing air micro-bubbles. Finally, we confirmed that the spatial resolution of the system estimated from the obtained CT images does not contradict the result of the evaluation formula of spatial resolution including the effect of X-rays diffraction.